2017
DOI: 10.3233/jad-170473
|View full text |Cite
|
Sign up to set email alerts
|

An Overview of Human Immunodeficiency Virus Type 1-Associated Common Neurological Complications: Does Aging Pose a Challenge?

Abstract: With increasing survival of patients infected with human immunodeficiency virus type 1 (HIV-1), the manifestation of heterogeneous neurological complications is also increasing alarmingly in these patients. Currently, more than 30% of about 40 million HIV-1 infected people worldwide develop central nervous system (CNS)-associated dysfunction, including dementia, sensory, and motor neuropathy. Furthermore, the highly effective antiretroviral therapy has been shown to increase the prevalence of mild cognitive fu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
8
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 280 publications
(277 reference statements)
1
8
0
Order By: Relevance
“…HIV infection causes acquired immunodeficiency syndrome (AIDS) affecting multiple systems in the body. One of the complications of HIV infection is the HIV-associated neurodegenerative disorder (HAND) (Navia et al, 1986), which can develop into HIV-associated dementia (Nookala et al, 2017), the most common cause of dementia in young adults (Janssen et al, 1992) with higher prevalence among women (Duarte et al, 2020). HIV is transported to the brain with infected T-lymphocytes and monocytes (Wiley et al, 1986;Takahashi et al, 1996).…”
Section: Hiv-associated Neurodegenerative Disordermentioning
confidence: 99%
See 2 more Smart Citations
“…HIV infection causes acquired immunodeficiency syndrome (AIDS) affecting multiple systems in the body. One of the complications of HIV infection is the HIV-associated neurodegenerative disorder (HAND) (Navia et al, 1986), which can develop into HIV-associated dementia (Nookala et al, 2017), the most common cause of dementia in young adults (Janssen et al, 1992) with higher prevalence among women (Duarte et al, 2020). HIV is transported to the brain with infected T-lymphocytes and monocytes (Wiley et al, 1986;Takahashi et al, 1996).…”
Section: Hiv-associated Neurodegenerative Disordermentioning
confidence: 99%
“…HIV is transported to the brain with infected T-lymphocytes and monocytes (Wiley et al, 1986;Takahashi et al, 1996). These long-lived cells are referred to as sources of HIV chronic infection (Nookala et al, 2017). In the brain, HIV infects primarily the immunocompetent cells, perivascular macrophages, and microglia where it replicates (Watkins et al, 1990;Albright et al, 2000).…”
Section: Hiv-associated Neurodegenerative Disordermentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, this study utilized female mice, whereas most MPTP studies are performed in male mice to reduce known variability observed with females. With the advent of ART for HIV-1 treatment, individuals living with HIV have longer lives with fewer co-morbidities, yet still can exhibit motor deficits like PD [176][177][178][179][180]. Thus, a major, yet recurrent question is whether HIV infection affects the development of PD-linked neurodegeneration.…”
Section: Parkinson's Diseasementioning
confidence: 99%
“…Although the prevalence of asymptomatic neurocognitive impairment without functional impairment may have been overestimated in the presence of too lenient neuropsychological guidelines (Gisslen, Price, & Nilsson, 2011), it has become evident over the years that there is considerable heterogeneity in pattern and severity of cognitive and motor deficits in the HIV population. Some individuals demonstrate moderate deficits in multiple domains, whereas others demonstrate little to no observable deficits (Nookala, Mitra, Chaudhari, Hegde, & Kumar, 2017). Further, a new challenge looms as individuals living with HIV infection age, with older individuals at greater risk of developing cognitive and motor deficits than are older individuals without HIV infection (Elicer, Byrd, Clark, Morgello, & Robinson‐Papp, 2018; Goodkin et al ., 2017; Sheppard, Woods, et al ., 2015; Smail & Brew, 2018).…”
Section: Introductionmentioning
confidence: 99%